2015
DOI: 10.1080/10807039.2015.1017874
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Risk Assessment Associated with Intake of Pesticide Residues in Food of Plant Origin from the Retail Market in Poland

Abstract: The aim of this study was to characterize short-and long-term risk for consumers associated with dietary intake of pesticide residues in fruits, vegetables, and other foodstuffs available on the Polish market based on 2010-2013 official surveillance results. Among 779 samples collected from 2010 to 2013 no pesticide residue was found in 39.7% samples while 58.5% contained residues at or below the EU Maximum Residue Levels (MRLs). Non-compliances (residues above the respective MRLs) were found in 14 samples (1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A risk assessment study of pesticide residues in Chinese pears performed by Li et al [34] showed a potential acute risk for children generated by the presence of bifenthrin. Struci ński et al [37] concluded that chronic exposure related to pesticide residues present in different fruits and vegetables available on the Polish market was lower than the toxicological reference values. Mebdoua et al [38] provided important results addressing the consumers from Algeria, regarding the short-and long-term risk assessment associated with the presence of chlorpyrifos in apples and potatoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A risk assessment study of pesticide residues in Chinese pears performed by Li et al [34] showed a potential acute risk for children generated by the presence of bifenthrin. Struci ński et al [37] concluded that chronic exposure related to pesticide residues present in different fruits and vegetables available on the Polish market was lower than the toxicological reference values. Mebdoua et al [38] provided important results addressing the consumers from Algeria, regarding the short-and long-term risk assessment associated with the presence of chlorpyrifos in apples and potatoes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the highest exceedance of the toxicological reference values occurred for procymidone in lettuce [28]. Struci ński et al [37] performed a risk assessment associated with dietary intake in vegetables, fruits and other food products from the Polish market, considering both chronic and acute exposure. Potential exceedance of the toxicological reference values was examined in the case of short-term exposure scenario for chlormequat in pears (425% of ARfD for children and 100.2% of ARfD for adults) and for carbendazim in lettuce (76.7% of ARfD for children, and 31.3% of ARfD for adults).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that carbendazim and methomyl exhibited a potential risks to children, while methomyl posed a potential risk to adults [79]. An acute risk assessment study on Polish vegetables also showed potentially hazardous contingencies [80]. Zuo [82,83].…”
Section: Acute Dietary Risk Assessment Of Two Major Leafy Vegetablesmentioning
confidence: 94%